The Position of Marketplace In Online Transactions And Mitigation of Unilateral Cancellations Based On Theory of Responsibility - Anisa Putri Wulandari; Reka Dewantara; Yenny Eta Widyanti (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The development of information technology has driven the growth of e-commerce through marketplaces as the primary means of online transactions in Indonesia. The presence of marketplaces not only simplifies the relationship between sellers and consumers but also raises various legal issues, particularly regarding the position of marketplaces and the practice of unilateral transaction cancellations. This study aims to analyze the position of marketplaces in online transactions based on the theory of responsibility and analyze forms of mitigation and accountability for unilateral cancellations in online buying and selling transactions. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials analyzed qualitatively using deductive reasoning. The results show that marketplaces can no longer be viewed merely as digital intermediaries, but rather as electronic system organizers actively involved in the electronic transaction process. This involvement has legal consequences in the form of marketplace liability for user losses, particularly due to unilateral transaction cancellations, system failures, or negligence in platform supervision. In addition, mitigation of unilateral cancellations needs to be carried out through strengthening marketplace supervision systems, information transparency, consumer protection, and the provision of effective dispute resolution mechanisms. Therefore, clearer legal regulations are needed regarding the position and responsibilities of marketplaces to create legal certainty, consumer protection, and a fair and sustainable digital trading system in Indonesia.